(untitled) (Sciences & Technology. A, exactes sciences, 2002)
In this work we are interested in a certain class of equations with operator coefficients and non-local boundary conditions. For the boundary value problem generated by these equations we establish the existence and uniqueness of the strong solution as well as its continuous dependence on the data. We use the method of energy inequality.